THE INFLUENCE OF THINK-PAIR-SHARE TECHNIQUE (TPS) TO TEACH READING COMPREHENSION TO THE TENTH GRADE STUDENTS - Ariski, Sri; Rositasari, Tri; Saraswaty, Dwi Rara (Universitas Muhammadiyah Palembang, 2021)
The objective of this study was to find out the influence of TPS to teach reading comprehension to the Tenth Grade Students at SMA Negeri 1 Sekayu. The subject of this study was the tenth-grade students at SMA Negeri 1 Sekayu in academic year 2019/2020 which amounted to 64 students’ representatives of 193 populations. This study was a quantitative research. This study used quasi-experimental method. The research design used two groups pretest posttest design. The test consisted 30 items in multiple choices. The result of test was calculated by using SPSS Software22. The alternative hypothesis (Ha) was examined through the test. Based on the criteria of testing hypotheses, the alternative (Ha) 5% significance level was t- obtained of the test. It means that teaching reading comprehension by using TPS technique to the Eighth-Grade students of SMA Negeri 1 Sekayu in the academic year 2020 was effective.